2015
DOI: 10.1039/c5gc00828j
|View full text |Cite
|
Sign up to set email alerts
|

Anion exchange capacity of biochar

Abstract: Biochar has gained recent interest as a soil amendment and agent for carbon sequestration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
88
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(91 citation statements)
references
References 69 publications
(125 reference statements)
2
88
1
Order By: Relevance
“…Spectra were fitted with Gaussian functions. As exemplified by the RF system, oxygen in all C(and EC)-RES-O(or D) was in equal amounts in the form of heteroaromatic pyrylium (O + at about 533 eV), [41] and charge-compensating phenoxide groups (O − at about 532 eV), [42,43] as published recently for the C aerogels. [35] Oxygen in C(and EC)-PBO was also in the form of pyrylium and CO -, whereas the latter probably overlaps with some CO also at around 532 eV, [44,45] hence the somewhat highest intensity peak.…”
Section: Methodsmentioning
confidence: 94%
“…Spectra were fitted with Gaussian functions. As exemplified by the RF system, oxygen in all C(and EC)-RES-O(or D) was in equal amounts in the form of heteroaromatic pyrylium (O + at about 533 eV), [41] and charge-compensating phenoxide groups (O − at about 532 eV), [42,43] as published recently for the C aerogels. [35] Oxygen in C(and EC)-PBO was also in the form of pyrylium and CO -, whereas the latter probably overlaps with some CO also at around 532 eV, [44,45] hence the somewhat highest intensity peak.…”
Section: Methodsmentioning
confidence: 94%
“…Corn stover, red oak ( Quercus rubra L., RO), and CE (99% pure, from Sigma Aldrich) were used as biomass feedstocks to produce biochars in this study; because CS represents herbaceous feedstocks, RO represents woody feedstocks, and CE is a nearly pure material, which simplifies interpretations of chemical and spectroscopic evidence (Lawrinenko and Laird, 2015). Biochars were produced from CS, RO, and CE biomasses by slow pyrolysis using a programmable muffle furnace that heated biomass to highest treatment temperatures of 400, 500, 700, and 900°C under a N 2 purge (100 mL min −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…None of these studies offered an explanation for the type of functional groups responsible for the positive surface charge on biochar surfaces. Lawrinenko and Laird (2015) were the first to investigate the nature of the positively charged functional groups on biochar surfaces. They reported that positive charge on biochar surfaces was due to pH-independent O heterocycles (oxonium groups) and, to a lesser extent, to pH-dependent N heterocycles (pyridinium groups) and condensed aromatic C, which may abstract protons from aqueous solutions at low pH.…”
Section: Impact Of Pyrolysis Temperature and Feedstock On Surface Chamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the existence of base functional groups including chromenes, ketones and pyrones on biochar can facilitate NO 3 --N adsorption to biochar (Montes- Morán et al, 2004;Amonette & Joseph, 2009). NO 3 --N adsorption is also possible via unconventional H-bonding between NO 3 --N ions and the biochar surface (Mukherjee et al, 2011;Lawrinenko, 2014;Kammann et al, 2015).…”
mentioning
confidence: 99%